Lack of association between aryl hydrocarbon receptor gene Arg554Lys polymorphism and male infertility risk: A systematic review and meta-analysis. (April 2018) - Wei, Yong; Zhang, Zheng; Chen, Guotao; Zhu, Leilei; Jiang, Hesong; Yang, Baibing; Chen, Yun; Dai, Yutian; Chen, Quanbing
Abstract: Objectives: The association between aryl hydrocarbon receptor gene (AhR) polymorphism and male infertility risk remains conflicting. We conducted a meta-analysis to examine the AhR Arg554Lys polymorphism in relation to the susceptibility to male infertility. Study design: Studies concerning the association between AHR polymorphism and male infertility were searched and related information were extracted from the included studies. The STATA 12.0 software was used to perform a meta-analysis. Pooled odd ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated to estimate the association. Results: Six case-control studies with 1234 cases and 1755 controls were included after literature research and data collection. Overall, the results indicated there was no association between the AhR Arg554Lys polymorphism and male infertility risk (G versus A, OR (95%CI) = 0.958 (0.710–1.291); GG vs AA, OR (95%CI) = 0.874 (0.702–1.088); GA versus AA, OR (95%CI) = 0.911(0.477–1.740); GG + GA vs AA, OR (95%CI) = 0.891 (0.468–1.696); GG versus GA + AA, OR (95%CI) = 1.049(0.896–1.229)). Subgroup analysis by study population revealed there was no association between AhR Arg554Lys polymorphism and susceptibility to male infertility in Asian population (G versus A, OR (95%CI) = 1.099 (0.940–1.286); GG vs AA, OR (95%CI) = 0.982 (0.781–1.235); GA versus AA, OR (95%CI) = 1.220 (0.726–2.052); GG + GA vs AA, OR (95%CI) = 1.221 (0.740–1.982); GG versus GA + AA, OR (95%CI) = 1.087 (0.919–1.286)). Conclusions: The association between AHR Arg55Lys polymorphism and male infertility risk was not confirmed in our meta-analysis. However, the results should be interpreted with caution and further studies are required.